Semiotic Analysis of the Representation of Family Conflict in the Film Home Sweet Loan - Andhika Setyagama; Ike Desi Florina; Sarwo Edy (LPPM Institut Pendidikan Nusantara Global, 2026)
This study examines the representation of family conflict in the film Home Sweet Loan using Charles Sanders Peirce’s semiotic approach. Family conflict is understood as an unavoidable social reality, often triggered by unequal role distribution, miscommunication, and economic pressure. The film Home Sweet Loan was chosen as the object of analysis because it portrays the emotional struggles of Kaluna, a young woman who faces various forms of domestic tension, including unequal household responsibilities, financial burdens stemming from her brother’s debt, and limited personal space in her extended family home. This research employs a qualitative descriptive method through close observation of seven selected scenes, which were analyzed using Peirce’s triadic model consisting of representamen, object, and interpretant. The findings reveal that the film represents three categories of family conflict as classified by Joseph A. Devito; role conflict, resource conflict, and communication conflict. Imbalanced expectations, competition over limited family resources, and unilateral decision-making create emotional strain that shapes the narrative trajectory. Visual signs and symbolic elements in the film effectively illustrate Kaluna’s psychological burden and the unequal distribution of familial roles. The study concludes that Home Sweet Loan serves not only as entertainment but also as a form of social reflection, emphasizing the importance of open communication, empathy, and fairness in maintaining harmony within the family.